First Francisella novicida Case Report in Argentina - Vilches, Viviana (2023)
The authors present a case report caused by Francisella novicida, a rare opportunistic human pathogen that may cause a tularemia-like disease in patients who are immunocompromised. The diagnosis is a challenge since it can be confused with Pasteurella or Brucella, and matrix-assisted laser desorption ionisation time-offlight systems are limited due to its poor performance in identification.